The Biomechanical Properties of Cement-Augmented Pedicle Screws for Osteoporotic Spines. Issue 2 (March 2022) - Wang, Yuetian; Yang, Lei; Li, Chunde; Sun, Haolin
Study Design: This is a broad, narrative review of the literature. Objective: In this review, we describe recent biomechanics studies on cement-augmented pedicle screws for osteoporotic spines to determine which factors influence the effect of cement augmentation. Methods: A search of Medline was performed, combining the search terms "pedicle screw" and ("augmentation" OR "cement"). Articles published in the past 5 years dealing with biomechanical testing were included. Results: Several factors have been identified to impact the effect of cement augmentation in osteoporotic spines. These include the type of augmentation material, the volume of injected cement, the timing of augmentation, the severity of osteoporosis, the design of the pedicle screw, and the specific augmenting technique, among others. Conclusions: This review elaborates the biomechanics of cement-augmented pedicle screws, determines which factors influence the augmentation effect, and identifies the risk factors of cement leakage in osteoporotic bone, which might offer some guidance when using this technique in clinical practice. Further, we provide information about newly designed screws and recently developed augmentation materials that provide higher screw stability as well as fewer cement-related complications.